Persuasive Technology 11th International Conference, PERSUASIVE 2016, Salzburg, Austria, April 5-7, 2016, Proceedings - Meschtscherjakov, Alexander; De Ruyter, Boris; Fuchsberger, Verena; Murer, Martin; Tscheligi, Manfred (Information Systems and Applications, incl. Internet/Web, and HCI, 2016)
This book constitutes the refereed proceedings of the 11th International Conference on Persuasive Technology, PERSUASIVE 2016, held in Salzburg, Austria, in April 2016. The 27 revised full papers and 3 revised short papers presented were carefully reviewed and selected from 73 submissions. The papers are grouped in topical sections on individual differences, theoretical reflections, prevention and motivation, methods and models, games and gamification, interventions for behavior change, and design strategies and techniques.